2008
DOI: 10.1111/j.1365-2729.2008.00277.x
|View full text |Cite
|
Sign up to set email alerts
|

Are high‐coherent concept maps better for prior knowledge activation? Differential effects of concept mapping tasks on high school vs. university students

Abstract: We investigated whether and how prior knowledge activation improves learning outcomes for high school (less experienced learners) and university students (experienced learners) in a hypertext environment. Map coherence was defined as the extent to which relationships between the concepts in the map were made explicit. Therefore, we classified the mapping task of creating and labelling lines as low-coherent, and the mapping task of labelling provided lines as high-coherent. Learners were randomly assigned to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0
4

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(49 citation statements)
references
References 45 publications
1
38
0
4
Order By: Relevance
“…31 In the application of concept maps, the pre-knowledge of the concepts included in the map is important. This is confirmed by research conducted by Gurlitt and Renken, 32 which showed that the use of concept maps triggered the necessary pre-knowledge. The linking of concepts in maps facilitated learning with understanding, and, consequently, the synthesis of knowledge, which also affected the attitude of students to chemistry.…”
Section: Introductionsupporting
confidence: 68%
“…31 In the application of concept maps, the pre-knowledge of the concepts included in the map is important. This is confirmed by research conducted by Gurlitt and Renken, 32 which showed that the use of concept maps triggered the necessary pre-knowledge. The linking of concepts in maps facilitated learning with understanding, and, consequently, the synthesis of knowledge, which also affected the attitude of students to chemistry.…”
Section: Introductionsupporting
confidence: 68%
“…One possible explanation is that participants in the low-coherence condition were not able to use organization and model construction processes to compensate for less structure in the map and less elaboration processes during prior knowledge activation. Related research using the same tasks in the domain of physics supports this view (Gurlitt and Renkl 2008). The latter research showed that although learners in the low-coherence condition asked more model-construction questions, only learners with a higher level of expertise (physics major students versus high-school students) were able to benefit from the low-coherence prior knowledge activation.…”
Section: Discussionmentioning
confidence: 74%
“…Concept mapping has been used effectively for some time as a tool to facilitate meaning-making in science (Novak, Gowin, & Johansen, 1983), help students make their prior knowledge and understandings of science explicit (Gurlitt & Renkl, 2008), and to assist low-achieving students in improving their comprehension of science (Guastello, Beasley, & Sinatra, 2000). While an examination of Table 4 shows that there were significant differences between Experimental a , Experimental b , and the Comparison condition at Time 1 with Experimental a being only marginally better than Experimental b , by Time 2 there were no significant differences between any of the conditions (see Table 5) with students' scores in all conditions having improved markedly from Time 1 to Time 2 (see Figure 1).…”
Section: Discussionmentioning
confidence: 99%